Acute Effects of an Ergometer-Based Dryland Alpine Skiing Specific High Intensity Interval Training - Stöggl, Thomas; Kröll, Josef; Helmberger, Roland; Cudrigh, Maria; Müller, Erich (Frontiers in Physiology, 2018)
Introduction: To establish an alpine ski racing (ASR) specific dryland high intensity training protocol (HIT), we set out to analyze cardiorespiratory and metabolic responses of three ASR specific HIT modes using a ski ergometer compared with a running HIT. Methods: Ten healthy international FIS level subjects (18 ± 1 years) performed an incremental running VO2max test, three different ASR specific HIT modes [slalom (SL), giant slalom (GS), and SL/GS mix] and a running HIT with measurements of VO2, heart rate (HR), blood lactate, and rate of perceived exertion (RPE). The HIT protocols included 15 × 1-min intervals with >90% HRmax and 30 s active rest. Furthermore, one elite alpine skier performed an 8-week, 17 session HIT block using the SL/GS mixed mode. Results: Running HIT resulted in greater VO2peak and whole-body RPE compared with the three ASR-specific HIT modes. During all four exercise modes participants were able to reach exercise intensities high enough to be classified as HIT (>90% HRmax and >89% VO2max). Legs RPE was similar between the four HIT modes, while arms RPE was higher for the ski-specific HIT. For all studied parameters, similar results for the three skiing specific HIT modes were observed. The 8-week HIT block was feasible for the athlete and resulted in an 11% increase in VO2max at unchanged peak power output. Conclusion: Across all HIT protocols high cardiorespiratory and metabolic responses were achieved. Therefore, the ASR specific HIT was shown to be feasible, thus could offer new possibilities for endurance training in elite alpine skiers. It is suggested to use the SL/GS mixed mode in terms of movement variety. The reduced VO2 in the ski-specific modifications can be attributed to the concentric and eccentric muscle activity resulting in mechanical hindrance for O2 extraction. The long-term effectiveness of ASR specific HIT in elite alpine skiers needs to be proven in a future study.